Constructing Bangladesh : religion, ethnicity, and language in an Islamic nation - Uddin, Sufia M. (Chapel Hill : University of North Carolina Press, 2006)
"Highlighting the dynamic, pluralistic nature of Islamic civilization, Sufia Uddin examines the complex history of Islamic state formation in Bangladesh, formerly the eastern part of the Indian province of Bengal. Uddin focuses on significant moments in the region's history from medieval to modern times, examining the interplay of language, popular and scholarly religious literature, and the colonial experience as they contributed to the creation of a unique Bengali-Islamic identity."--BOOK JACKET.
1. Islamic themes in premodern Bengali literature and life -- 2. Nineteenth-century religious reform movements -- 3. Breaking new ground and transgressing boundaries -- 4. Bengali or Bangladeshi? : the conflict between religious and ethnic nationalisms -- 5. The contested place of nation in Umma and globalizing efforts -- Epilogue : competing visions of community.
Includes bibliographical references (p.[208]-216) and index.
Keywords: Islam and state -- Bangladesh -- History; Group identity -- Bangladesh -- History; Bengali language -- Social aspects; Nationalism -- Bangladesh -- History; Bangladesh -- History; Bangladesh -- Civilization